2022
DOI: 10.1002/eap.2760
|View full text |Cite
|
Sign up to set email alerts
|

Predictive accuracy of post‐fire conifer death declines over time in models based on crown and bole injury

Abstract: A key uncertainty of empirical models of post‐fire tree mortality is understanding the drivers of elevated post‐fire mortality several years following fire, known as delayed mortality. Delayed mortality can represent a substantial fraction of mortality, particularly for large trees that are a conservation focus in western US coniferous forests. Current post‐fire tree mortality models have undergone limited evaluation of how injury level and time since fire interact to influence model accuracy and predictor var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 91 publications
(157 reference statements)
0
1
0
Order By: Relevance
“…surface, crown) after wildfire extinction. Such knowledge would be of value, for example, in (1) testing the accuracy of fire behaviour models (Alexander and Cruz 2012), (2) providing insights on pre-fire fuel conditions conducive to extreme fire behaviour and severe ecological impacts (Dimitrakopoulos et al 2007), (3) evaluating fuel treatment effectiveness (Cruz et al 2004;Hu et al 2019), and (4) estimating post-fire ecosystem responses including delayed tree mortality (Shearman et al 2023). Indeed, several authors suggested that physically meaningful variables of actual fire effects that can be used as a proxy for fire type, such as crown fraction burned (CFB), can be more readily translated into management applications (Woolley et al 2012;Hood et al 2018), as opposed to integrative fire severity indices (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…surface, crown) after wildfire extinction. Such knowledge would be of value, for example, in (1) testing the accuracy of fire behaviour models (Alexander and Cruz 2012), (2) providing insights on pre-fire fuel conditions conducive to extreme fire behaviour and severe ecological impacts (Dimitrakopoulos et al 2007), (3) evaluating fuel treatment effectiveness (Cruz et al 2004;Hu et al 2019), and (4) estimating post-fire ecosystem responses including delayed tree mortality (Shearman et al 2023). Indeed, several authors suggested that physically meaningful variables of actual fire effects that can be used as a proxy for fire type, such as crown fraction burned (CFB), can be more readily translated into management applications (Woolley et al 2012;Hood et al 2018), as opposed to integrative fire severity indices (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Stem char height and percentage of bole char height have commonly been used as a proxies for potential cambium damage in post-fire mortality prediction [57,[79][80][81][82]. However, the use of these variables has been criticized due to their frequent poor or inconsistent performance [17,83,84]. Furthermore, stem char height has also been used as a proxy for flame length and fireline intensity [85].…”
Section: Introductionmentioning
confidence: 99%
“…Bark char severity [86], an indicator of char depth used in mortality prediction studies [16,57,70], has been found to be significantly related to the probability of cambium necrosis [8]. Crown scorch height and percentage of crown volume or length scorched are by far the most commonly used variables to predict post-fire tree mortality [83,87,88], both alone and in combination with stem char height [62,89]. Since crown scorch does not describe the actual amount of crown foliage or buds affected by fire [90], monitoring litterfall biomass [31,91] can also help to determine the level of crown damage and can serve as a proxy for fire severity.…”
Section: Introductionmentioning
confidence: 99%